Cell evolution and compressive properties of styrene–butadiene–styrene toughened and calcium carbonate reinforced polystyrene extrusion foams with supercritical carbon dioxide. Issue 23 (22nd February 2016) - Jing, Xin; Peng, Xiang‐Fang; Mi, Hao‐Yang; Wang, Yuan‐Sheng; Zhang, Shuidong; Chen, Bin‐Yi; Zhou, Hua‐Min; Mou, Wen‐Jie
ABSTRACT: Polystyrene (PS) foams have been used in various fields, whereas its broader application is limited by its low mechanical strength and brittle features. In this study, styrene–butadiene–styrene (SBS) and calcium carbonate (CaCO3 ) nanoparticles were melt‐blended with PS and extrusion‐foamed with supercritical carbon dioxide as a blowing agent to simultaneously toughen and reinforce PS foams. Under the same foaming conditions, the addition of SBS and CaCO3 was shown to have a significant influence on the cell structure and the compressive properties of the composite foams. We found that the cell structure evolution was highly correlated with the system viscosity. When the rubbery‐phase SBS content was 20%, the cell diameter decreased by 20.7%, and the compressive modulus was enhanced by 289.5%. With the further addition of 5% rigid CaCO3 nanoparticles, the cell diameter was further reduced by 72.2% and the compressive modulus was improved by 379.2%. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43508. Abstract :